AT 89S51 MICROCONTROLLER IMPLEMENTATION CASE STUDY WITH CALCULATIONS ONFREQUENCY TONES - Firmansyah Manthovani; Fivtatianti Hendajani, SKom, MM (Jurnal Sistem Komputer, 2006)
AT 89S51 microcontroller is a system that can combine the input and output digital signals that can be used for various purposes, especially in industrial. With AT 89S51 microcontroller devices using a system that could be restrained in a compact and reliable because AT 89S51 microcontroller has a privilege in terms of hardware.With these features is support for technological advances in digital control systems are very efficientand effective. AT 89S51 microcontroller system is the control center of the overall work of existing circuits.Among the advantages compared to the use of microprocessors and microcontrollers AT 89S51 is already there in the microcontroller RAM and an intermediary of I/O and thus no longer supporting the addition of an intermediary I/O again, in addition to applying a device would be much simpler.For data processing in the system AT 89S51 microcontroller using assembly language.